IMPORTANCE OF ORGANIZATIONAL COMMITMENT, MOTIVATION AND INCENTIVES IN IMPROVING EMPLOYEE PERFORMANCE - Darmin Darmin; Abdullah Muksin; Yosandy Yulius (Dinasti International Journal of Education Management And Social Science, 2021)
The purpose of this reseach was to determine the Effect of Motivation, Incentives and Organizational Commitment on Employee Performance of Garment companies in north jakarta. The research method is descriptive method. The sampe ini this reseach amounted to 107 respondents of Garment companies in north jakarta employees. Data processing uses quantitative data analysis using SPSS 25.0 for windows. The results showed that the determinant coefficient (Adjuster R Square) of 0.772 means that the variables of Motivation, Incentives and Organizational Commitment together contributed to the Performance of 77.2%, the remaining 22.8% were other variables not in the model. The results of multiple regression show that both Motivation, Incentive and Organizational Commitment variables have a positive influence on Employee Performance. Significant value of 0,000<0,005 and Fcount>Ftable (71,162>2,761) which means that there is a significant relationship between Motivation, Incentives and Organizational Commitment and Employee Performance.